Flint Hills Night Sky ; and, Imagine - H. C. Palmer (Symphony in the Flint Hills, 2010)
A story asking you to visualize the beauty of the prairie and the simple bits of nature. Includes the image "The Flint Hills Night Sky - Early Summer."
Keywords: stars; night; sky; moon; shadows; poem; landscape; nature; Flint Hills